PENGENALAN LITERASI DASAR KOMPUTER DAN MICROSOFT WORD SEBAGAI UPAYA MELATIH KETERAMPILAN SISWA SDN 3 TANJUNG LAGO - Fitria Pratiwi; Tri Oktarina (Abdi Jurnal Publikasi, 2025)
The rapid development of information and communication technology has greatly influenced the education sector, especially in the integration of digital literacy from an early age. This community service activity introduces basic computer literacy and Microsoft Word to 4th-grade students at SDN 3 Tanjung Lago, Banyuasin. The aim is to enhance students' skills and confidence in using technology to support learning in the digital era. The method used includes interactive lectures, demonstrations, group practice, and individual tasks. Despite limitations in infrastructure and students' initial knowledge, the activity received a positive response from both students and teachers. The result shows that students demonstrated increased enthusiasm and basic proficiency in operating computers and Microsoft Word. The activity is expected to be sustainable as a foundation for developing 21st-century skills in rural elementary school students.